Motivating students on ICT-related study programs to engage with the subject of sustainable development. Issue 3 (5th March 2018) - Hilty, Lorenz M.; Huber, Patrizia
Abstract : Purpose: Sustainable development (SD) does not usually form part of the curriculum of ICT-related study programs such as Computer Science, Information Technology, Information Systems, and Informatics. However, many topics form a bridge between SD and ICT and could potentially be integrated into ICT-related study programs. This paper reports the findings of a study into which specific topics in the field of SD have the greatest potential to motivate students on ICT-related study programs to engage with the topic of sustainability. Design/methodology/approach: In this exploratory study, the authors evaluated Bachelor's and Master's courses that introduced the topic of SD to students on ICT-related study programs. The evaluation focuses on the insights that the students gained into sustainability and the extent to which their motivation to engage with the subject was increased. The evaluation combines qualitative and quantitative approaches. Findings: The authors identify five thematic clusters with the greatest potential to motivate students to engage with the topic of sustainability: A conceptual model of the positive and negative impacts of ICT; Reports on the recycling of ICT hardware; Examples of using ICT to reduce greenhouse gas emissions with a focus on the substitution of virtual for physical presence; Statistical data on post-industrial seemingly dematerialized economies and the contradiction with regard to the total material demand of such economies; Evidence for rebound effects that lead to increasing demand for goods or services that are produced with less energy input or can be consumed faster. Originality/value: ICT is a transformational and to a certain extent disruptive technology. It is therefore important to discuss the development of ICT and its applications in the context of SD. Several authors have pointed out the need to integrate the topic of sustainability into ICT courses at universities and similar, but few have discussed how this can be done in practice. Our study is the first to explore which topics have the greatest potential to motivate students on ICT-related programs to engage with the area of SD.